The Effect of Budget Planning, Budget Implementation and Human Resources Competency on Budget Absorption in Bukittinggi City Regional Government - Putri, Anne; Herawati, Novi (ADPEBI, 2022)
This study aims to determine how the influence of budget planning, budget execution and human resource competence on budget absorption in the of Government Bukittinggi City. This research was conducted at the Local Government Organization of the City of Bukittinggi. The research method used is quantitative data analysis. The sample determination technique uses a purposive sampling technique, namely 11 regional apparatus organizations that are sampled, namely regional apparatus organizations whose budget realization at the end of 2020 is less than 91%. The target population of the study were Budget Users (BU), Budget User Authorizations (BUA), Head of Planning and/or Finance Subdivision, Technical Implementation Officers (TIO), and Expenditure Treasurers in each Regional Apparatus Organization, so the total sample was 55 respondents. The method of data collection was done by questionnaire, multiple regression analysis using the Smart PLS program. The results showed that Budget Planning, Budget Execution had a positive and significant effect on Budget Absorption, while Human Resource Competence had a positive but not significant effect on Budget Absorption in the Bukittinggi City Government